1972
DOI: 10.1128/aac.2.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isoniazid on the In Vivo Mycolic Acid Synthesis, Cell Growth, and Viability of Mycobacterium tuberculosis

Abstract: When an actively growing culture of the H37Ra strain of Mycobacterium tuberculosis was exposed to isoniazid at a concentration of 0.5 ,g/ml, the cells began to lose their ability to synthesize mycolic acids immediately. After 60 min, the cells had completely lost this ability. The synthesis of the three mycolate components-amycolate, methoxymycolate, and f-mycolate-was inhibited. The viability of the isoniazid-treated cells was unaffected up to about 60 min of exposure, after which time there was a gradual dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
173
1
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(190 citation statements)
references
References 27 publications
(25 reference statements)
9
173
1
4
Order By: Relevance
“…Isoniazid was shown to inhibit the biosynthesis of mycolic acids (29), and the reductases involved in fatty-acid elongation isolated from Mycobacterium avium were shown to be selectively inhibited by the drug (17). More recent work has shown that the reductases are the targets of isoniazid inhibition in M. tuberculosis (1,25).…”
Section: Discussionmentioning
confidence: 99%
“…Isoniazid was shown to inhibit the biosynthesis of mycolic acids (29), and the reductases involved in fatty-acid elongation isolated from Mycobacterium avium were shown to be selectively inhibited by the drug (17). More recent work has shown that the reductases are the targets of isoniazid inhibition in M. tuberculosis (1,25).…”
Section: Discussionmentioning
confidence: 99%
“…Purification of the complex will be required to determine its precise nature. On the basis of the high sensitivity of the KasA-containing complex to alkaline pH (13), 5 it is tempting to hypothesize that the AcpM phosphopantetheine prosthetic group is directly involved in the covalent linking of AcpM and KasA. The phosphodiester group that links the prosthetic group to Ser-41 of AcpM 5 is the most chemically sensitive bond in the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Middlebrook (3) was the first to carefully quantify the bactericidal activity of INH. Although Winder and Collins (4) demonstrated that INH inhibits mycolic acid biosynthesis, Takayama et al (5) demonstrated that inhibition of mycolic acid biosynthesis correlates with cell death. Takyama et al (6) further demonstrated that the inhibition of mycolic acid biosynthesis mediated by INH leads to the accumulation of a saturated C 26 fatty acid within 1 h of INH treatment.…”
Section: Isoniazid (Inh)mentioning
confidence: 99%
“…Indeed, the cessation of mycolic acid synthesis is one of the primary effects of isoniazid (INH), 1 a front-line anti-tuberculosis drug (13). Various other compounds including ethionamide (14,15), isoxyl (15,16), and thiolactomycin (TLM) (17), have also been shown to inhibit mycolic acid synthesis.…”
mentioning
confidence: 99%